SOSIALISASI EDUKASI PENGGUNAAN VITAMIN NEUROTROPIK BAGI MASYARAKAT DESA KWALA SIMEME KECAMATAN NAMORAMBE - Simorangkir, Delisma Marsauli (INSTITUT KESEHATAN DELI HUSADA, 2025)
This Community Service Activity aims to socialize the pharmacist profession and educate the people of Kwala Sime Village, Namorambe District. Neuropathy is a condition that requires serious attention, and early treatment is essential to improve the patient's quality of life. Education about neuropathy and the use of B complex vitamins, consisting of vitamins B1, B6, and B12, is expected to increase public awareness of the importance of treating this disease. This activity involved students of the Pharmacist Professional Study Program of the Deli Husada Deli Tua Health Institute as extension workers, and was held on May 6, 2025. The results of this activity show an increase in public understanding of the role of pharmacists and the benefits of neurotrophic vitamins, as well as encouraging people to pay more attention to their neural health. This activity is expected to continue to provide further education to the community.